Preparation method of light low-thermal-conductivity lutetium silicate aerogel
Through composite sol preparation and supercritical drying processes, the problem of preparation of letetium silicate aerogels is solved, and lightweight, low thermal conductivity, high porosity and high temperature thermal stability is achieved. It is suitable for high-temperature heat insulation materials.
Patent Information
- Application Number
- CN202411918671.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
AI Technical Summary
The lack of a method for preparing letetium silicate aerogels in the prior art has resulted in limited application of the material in high temperature environments.
Lightweight, low heat conductivity of lete-silicate aerogels were prepared by composite sol preparation, wet gel aging, supercritical drying or frozen vacuum drying and calcining treatment.
It has achieved high porosity, low thermal conductivity and high temperature thermal stability of lemate silicate aerogel, and can be used at extreme temperatures of 1500°C. It is suitable for ceramic aerogel thermal insulation materials.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous material preparation technology, and specifically to a method for preparing a lightweight and low-thermal-conductivity lutetium silicate aerogel. Background Art
[0002] Rare earth silicates have high melting points (generally above 1500°C), extremely low high-temperature oxygen permeability, low Young's modulus, low thermal conductivity, low saturated vapor pressure and other physical and chemical properties, and have good phase stability. The structure of the material determines its intrinsic properties, which in turn affects the application of the material. The crystal structure of Lu2O3.SiO2 is relatively simple. With the increase of SiO2 content, lutetium silicate mainly exists in two crystal forms: Lu2SiO5 and Lu2Si2O7.
[0003] Both Lu2SiO5 and Lu2Si2O7 have only a single phase composition, and will not undergo phase changes during service, and can maintain the stability of the chemical structure. According to experimental calculations, the monoclinic phase of Lu2Si2O7 can remain stable above 1600°C. In addition, rare earth silicates also have low SiO2 activity and low volatility in engine service environments, so their environmental stability is significantly better than that of mullite materials. Lutetium silicate aerogel has excellent properties such as high thermal stability, low thermal conductivity, low thermal expansion coefficient, oxidation resistance and corrosion resistance. Compared with the widely used traditional oxide aerogel, it can be used in a higher temperature (>1300°C) environment. In addition, compared with non-oxide aerogels such as silicon carbide and silicon nitride, lutetium silicate aerogel can be used in higher temperatures and more severe oxidizing environments, so it can be used as an excellent new ceramic aerogel thermal insulation material. At present, most of the reports are about the preparation of lutetium silicate powder, and there are no reports on the preparation of lutetium silicate aerogel. Given that lutetium silicate aerogel ceramic materials with excellent high-temperature thermal stability are still lacking, it is very important to provide a simple and efficient method for preparing lutetium silicate aerogel. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a lightweight and low thermal conductive lutetium silicate aerogel to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a lightweight and low thermal conductivity lutetium silicate aerogel, comprising the following steps: S1: Preparation of composite sol: According to the chemical formula of lutetium silicate (Lu2SiO5 or Lu2Si2O7), weigh the lutetium source and silicon source precursors, add them into a container containing ethanol and water, add citric acid and continue stirring until completely hydrolyzed, and finally add propylene oxide and stir thoroughly to obtain a composite sol; S2: Preparation and aging of wet gel: Pour the composite sol into the mold, seal it and let it stand, add the aging liquid after it is completely gelled, and demold after aging is completed; S3: drying of gel: supercritical drying or freeze-vacuum drying of the wet gel prepared in S2 to obtain a dry gel; S4: Preparation of aerogel: The dry gel prepared in S3 is calcined to obtain Lu2SiO5 or Lu2Si2O7 ceramic aerogel.
[0006] Preferably, the lutetium source described in S1 is lutetium chloride hexahydrate (LuCl3·6H2O), lutetium nitrate pentahydrate [(Lu(NO3)3·6H2O], lutetium acetate (C6H 11 Lu7O7) or more.
[0007] Preferably, the molar ratio of lutetium source (equivalent to Lu2O3), silicon source precursor (equivalent to SiO2), ethanol, water, citric acid and propylene oxide in the Lu2SiO5 composite sol described in S1 is 1:1:(15-40):(6-15):(0.3-2.0):(6-8).
[0008] Preferably, the silicon source precursor in S1 is tetraethyl orthosilicate or methyl orthosilicate, or a combination of both.
[0009] Preferably, the molar ratio of lutetium source, silicon source precursor, ethanol, water, citric acid and propylene oxide in the composite sol of Lu2Si2O7 in S2 is 1:2:(15-40):(6-15):(0.3-2.0):(6-8).
[0010] Preferably, the aging time in S2 is 48 to 72 hours, and the aging solution is replaced every 6 to 12 hours.
[0011] Preferably, the aging liquid in S2 is one or a combination of ethanol, acetone, n-hexane or isopropanol.
[0012] Preferably, the supercritical drying in S3 is CO2 supercritical drying or freeze vacuum drying, the CO2 supercritical drying has a temperature of 32 to 50°C, a pressure of 9 to 12 MPa, and a drying time of 5 to 8 hours.
[0013] Preferably, the heat treatment temperature in S4 is 1200-1500° C., the heating rate is 1-20° C. / min, and the heat treatment time is 0.5-4 h.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares lutetium silicate aerogel by in-situ sol-gel combined with supercritical drying process. The material has high porosity and can be light, crack-free, complete block, and can be used for near-net-size molding.
[0015] The invention is easy to operate, can realize fluid production, and is easy to industrialize.
[0016] The lutetium silicate ceramic aerogel prepared by in-situ synthesis has higher porosity, better thermal stability and lower thermal conductivity, and can withstand extreme temperatures of 1500°C.
[0017] The present invention introduces citric acid as a structural support agent. Citric acid can form a stable soluble chelate with rare earth ions. Citric acid participates in coordination in the form of acid radicals by removing protons from carboxylic acids, thereby inhibiting the element loss of Lu3+ ions during aging replacement and supercritical drying, providing a guarantee for the formation of pure single-phase ceramic materials, reducing the volume shrinkage of the material caused by a large amount of organic matter during the calcination process, and increasing the specific surface area of the material. The prepared sample has the characteristics of high-temperature thermal stability, high porosity, low shrinkage, low density and low thermal conductivity, and can be light, crack-free and complete blocks. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The present invention provides a technical solution: a method for preparing a lightweight and low thermal conductivity lutetium silicate aerogel, comprising the following steps: S1: Preparation of composite sol: According to the chemical formula of lutetium silicate (Lu2SiO5 or Lu2Si2O7), weigh the lutetium source and silicon source precursors, add them into a container containing ethanol and water, add citric acid and continue stirring until completely hydrolyzed, and finally add propylene oxide and stir thoroughly to obtain a composite sol; S2: Preparation and aging of wet gel: Pour the composite sol into the mold, seal it and let it stand, add the aging liquid after it is completely gelled, and demold after aging is completed; S3: drying of gel: supercritical drying or freeze-vacuum drying of the wet gel prepared in S2 to obtain a dry gel; S4: Preparation of aerogel: The dry gel prepared in S3 is calcined to obtain Lu2SiO5 or Lu2Si2O7 ceramic aerogel. Example 1
[0020] (1) Weigh 0.03 mol of ethanol and 0.012 mol of water into a container and stir evenly. Use an electronic balance to accurately weigh lutetium chloride hexahydrate and tetraethyl orthosilicate and 0.0006 mol of citric acid according to the molar ratio of Lu2O3:SiO2=1:1, add them to the mixed solution of ethanol and water, stir until completely hydrolyzed, add 0.012 mol of propylene oxide and stir thoroughly to obtain a mixed sol; (2) pouring the mixed sol into a mold, sealing it and letting it stand for gelling, and then adding it to ethanol for aging. The aging time is 54 hours, and the aging solution is replaced every 6 hours to obtain the aged wet gel; (3) The sample was taken out and subjected to CO2 supercritical drying at a drying temperature of 35°C, a pressure of 9 MPa, and a drying time of 6 h to obtain a dry gel; (4) Finally, the dry gel is heat treated, and the heat treatment equipment includes: muffle furnace heat treatment temperature: 1300°C, insulation time: 3h, heating rate: 5°C / min, and Lu2SiO5 ceramic aerogel is obtained after the heat treatment is completed. Example 2
[0021] (1) Weigh 0.03 mol of ethanol and 0.012 mol of water into a container and stir evenly. Use an electronic balance to accurately weigh lutetium nitrate pentahydrate and tetraethyl orthosilicate and 0.0006 mol of citric acid according to the molar ratio of Lu2O3:SiO2=1:1, add them to the mixed solution of ethanol and water, stir until completely hydrolyzed, add 0.012 mol of propylene oxide and stir thoroughly to obtain a mixed sol; (2) pouring the mixed sol into a mold, sealing it and letting it stand for gelling, and then adding it to ethanol for aging. The aging time is 54 hours, and the aging solution is replaced every 6 hours to obtain the aged wet gel; (3) The sample was taken out and subjected to CO2 supercritical drying at a drying temperature of 35°C, a pressure of 9 MPa, and a drying time of 6 h to obtain a dry gel; (4) Finally, the dry gel is heat treated, and the heat treatment equipment includes: muffle furnace heat treatment temperature: 1300°C, insulation time: 3h, heating rate: 5°C / min, and Lu2SiO5 ceramic aerogel is obtained after the heat treatment is completed. Example 3
[0022] (1) Weigh 0.03 mol of ethanol and 0.012 mol of water into a container and stir evenly. Use an electronic balance to accurately weigh lutetium nitrate pentahydrate and tetraethyl orthosilicate and 0.0006 mol of citric acid according to the molar ratio of Lu2O3:SiO2=1:1, add them to the mixed solution of ethanol and water, stir until completely hydrolyzed, add 0.012 mol of propylene oxide and stir thoroughly to obtain a mixed sol; (2) pouring the mixed sol into a mold, sealing it and letting it stand for gelling, and then adding it to ethanol for aging. The aging time is 54 hours, and the aging solution is replaced every 6 hours to obtain the aged wet gel; (3) The sample was taken out and subjected to CO2 supercritical drying at a drying temperature of 35°C, a pressure of 9 MPa, and a drying time of 6 h to obtain a dry gel; (4) Finally, the dry gel is heat treated, and the heat treatment equipment includes: muffle furnace heat treatment temperature: 1300°C, insulation time: 3h, heating rate: 5°C / min, and Lu2SiO5 ceramic aerogel is obtained after the heat treatment is completed. Example 4
[0023] (1) Weigh 0.03 mol of ethanol and 0.012 mol of water into a container and stir evenly. Use an electronic balance to accurately weigh lutetium acetate and tetraethyl orthosilicate and 0.0006 mol of citric acid according to the molar ratio of Lu2O3:SiO2=1:1, add them to the mixed solution of ethanol and water, stir until completely hydrolyzed, add 0.012 mol of propylene oxide and stir thoroughly to obtain a mixed sol; (2) pouring the mixed sol into a mold, sealing it and letting it stand for gelling, and then adding it to ethanol for aging. The aging time is 54 hours, and the aging solution is replaced every 6 hours to obtain the aged wet gel; (3) The sample was taken out and subjected to CO2 supercritical drying at a drying temperature of 35°C, a pressure of 9 MPa, and a drying time of 7 h to obtain a dry gel; (4) Finally, the dry gel is heat treated, and the heat treatment equipment includes: muffle furnace heat treatment temperature: 1300°C, insulation time: 3h, heating rate: 5°C / min, and Lu2SiO5 ceramic aerogel is obtained after the heat treatment is completed. Example 5
[0024] (1) Weigh 0.06 mol of ethanol and 0.02 mol of water into a container and stir evenly. Use an electronic balance to accurately weigh lutetium chloride hexahydrate and tetraethyl orthosilicate and 0.002 mol of citric acid according to the molar ratio of Lu2O3:SiO2=1:2, add them to the mixed solution of ethanol and water, stir until completely hydrolyzed, add 0.015 mol of propylene oxide and stir thoroughly to obtain a mixed sol; (2) Pour the mixed sol into a mold, seal it and let it stand for gelation, then add it to ethanol for aging. The aging time is 54 hours, and the aging solution is replaced every 6 hours to obtain the aged wet gel; (3) The sample was taken out and subjected to CO2 supercritical drying at a drying temperature of 45°C, a pressure of 10 MPa, and a drying time of 6 h to obtain a dry gel; (4) Finally, the dry gel is heat treated, and the heat treatment equipment is: muffle furnace heat treatment temperature: 1300°C, insulation time: 4h, heating rate: 6°C / min. After the heat treatment is completed, Lu2Si2O7 ceramic aerogel is obtained. Example 6
[0025] (1) Weigh 0.06 mol of ethanol and 0.02 mol of water into a container and stir evenly. Use an electronic balance to accurately weigh lutetium nitrate pentahydrate and tetraethyl orthosilicate and 0.002 mol of citric acid according to the molar ratio of Lu2O3:SiO2=1:2, add them to the mixed solution of ethanol and water, stir until completely hydrolyzed, add 0.015 mol of propylene oxide and stir thoroughly to obtain a mixed sol; (2) Pour the mixed sol into a mold, seal it and let it stand for gelation, then add it to ethanol for aging. The aging time is 54 hours, and the aging solution is replaced every 6 hours to obtain the aged wet gel; (3) The sample was taken out and subjected to CO2 supercritical drying at a drying temperature of 45°C, a pressure of 10 MPa, and a drying time of 6 h to obtain a dry gel; (4) Finally, the dry gel is heat treated, and the heat treatment equipment is: muffle furnace heat treatment temperature: 1300°C, insulation time: 4h, heating rate: 6°C / min. After the heat treatment is completed, Lu2Si2O7 ceramic aerogel is obtained. Example 7
[0026] (1) Weigh 0.06 mol of ethanol and 0.02 mol of water into a container and stir evenly. Use an electronic balance to accurately weigh lutetium acetate and tetraethyl orthosilicate and 0.002 mol of citric acid according to the molar ratio of Lu2O3:SiO2=1:2, add them to the mixed solution of ethanol and water, stir until completely hydrolyzed, add 0.015 mol of propylene oxide and stir thoroughly to obtain a mixed sol; (2) Pour the mixed sol into a mold, seal it and let it stand for gelation, then add it to ethanol for aging. The aging time is 54 hours, and the aging solution is replaced every 6 hours to obtain the aged wet gel; (3) The sample was taken out and subjected to CO2 supercritical drying at a drying temperature of 45°C, a pressure of 10 MPa, and a drying time of 6 h to obtain a dry gel; (4) Finally, the dry gel is heat treated, and the heat treatment equipment is: muffle furnace heat treatment temperature: 1300°C, insulation time: 4h, heating rate: 6°C / min. After the heat treatment is completed, Lu2Si2O7 ceramic aerogel is obtained. Example 8
[0027] (1) Weigh 0.08 mol of ethanol and 0.03 mol of water into a container and stir evenly. Use an electronic balance to accurately weigh lutetium chloride hexahydrate and tetraethyl orthosilicate and 0.002 mol of citric acid according to the molar ratio of Lu2O3:SiO2=1:2, add them to the mixed solution of ethanol and water, stir until completely hydrolyzed, add 0.015 mol of propylene oxide and stir thoroughly to obtain a mixed sol; (2) Pour the mixed sol into a mold, seal it and let it stand for gelation, then add it to ethanol for aging. The aging time is 54 hours, and the aging solution is replaced every 6 hours to obtain the aged wet gel; (3) The sample was taken out and subjected to CO2 supercritical drying at a drying temperature of 50°C, a pressure of 12 MPa, and a drying time of 8 h to obtain a dry gel; (4) Finally, the dry gel is heat treated, and the heat treatment equipment is: muffle furnace heat treatment temperature: 1400°C, insulation time: 4h, heating rate: 6°C / min, and Lu2Si2O7 ceramic aerogel is obtained after the heat treatment is completed.
[0028] It is obvious to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive in all respects, and the scope of the invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims be included in the invention.
[0029] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a lightweight, low thermal conductivity lutetium silicate aerogel, characterized in that: The following steps are involved: S1: Preparation of composite sol: According to the chemical formula of lutetium silicate (Lu2SiO5 or Lu2Si2O7), weigh the lutetium source and silicon source precursors, add them into a container containing ethanol and water, add citric acid and continue stirring until completely hydrolyzed, and finally add propylene oxide and stir thoroughly to obtain a composite sol; S2: Preparation and aging of wet gel: Pour the composite sol into the mold, seal it and let it stand, add the aging liquid after it is completely gelled, and demold after aging is completed; S3: drying of gel: supercritical drying or freeze-vacuum drying of the wet gel prepared in S2 to obtain a dry gel; S4: Preparation of aerogel: The dry gel prepared in S3 is calcined to obtain Lu2SiO5 or Lu2Si2O7 ceramic aerogel.
2. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: The lutetium sources described in S1 are lutetium chloride hexahydrate (LuCl3·6H2O), lutetium nitrate pentahydrate [(Lu(NO3)3·6H2O], lutetium acetate (C6H 11 Lu7O7) or more.
3. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: The molar ratio of lutetium source (equivalent to Lu2O3), silicon source precursor (equivalent to SiO2), ethanol, water, citric acid and propylene oxide in the composite sol of Lu2SiO5 described in S1 is 1:1:(15~40):(6~15):(0.3~2.0):(6~8).
4. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: The silicon source precursor in S1 is tetraethyl orthosilicate or methyl orthosilicate, or a combination of both.
5. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: The molar ratio of lutetium source, silicon source precursor, ethanol, water, citric acid and propylene oxide in the composite sol of Lu2Si2O7 described in S2 is 1:2:(15-40):(6-15):(0.3-2.0):(6-8).
6. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: The aging time in S2 is 48 to 72 hours, and the aging solution is replaced every 6 to 12 hours.
7. The method for preparing the lightweight and low thermal conductive lutetium silicate aerogel according to claim 1, characterized in that: The aging liquid in S2 is one or a combination of ethanol, acetone, n-hexane or isopropanol.
8. The method for preparing the lightweight and low thermal conductive lutetium silicate aerogel according to claim 1, characterized in that: The supercritical drying in S3 is CO2 supercritical drying or freeze vacuum drying. The temperature of CO2 supercritical drying is 32-50°C, the pressure is 9-12MPa, and the drying time is 5-8h.
9. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: In S4, the heat treatment temperature is 1200-1500°C, the heating rate is 1-20°C / min, and the heat treatment time is 0.5-4h.
Citation Information
Cited By
Method for preparing ZrSiO4 aerogel by combining sol-gel with supercritical drying
CN120903557A
A method for preparing ZrSiO4 aerogel by sol-gel combined supercritical drying
CN120903557B